Applied pharmaceutical science and microbiology : novel green chemistry methods and natural products - Mahapatra, Debarshi Kar; Talele, Swati Gokul; Haghi, A. K. (Burlington, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2021)
"This volume on applied pharmaceutical science and microbiology looks at the latest research on the applications of natural products for drug uses. It focuses on understanding how to apply the principles of novel green chemistry methods in the vital area of pharmaceuticals and covers the important aspects of green microbial technology in the pharmaceutical industry. Chapters include studies on the applications used of natural products in folk and regional medicines, such as for digestive problems, dermatological infections, respiratory diseases, vessel diseases, diarrhea and dysentery, ringworms, boils, fevers (antipyretic), skin and blood diseases, mouth sores, channel discharges, and even cancer. It looks at medical benefit of microbial fermentation for the conservation of nutrients. Other chapters present information on AgNPs fabricated from natural plant and organism extracts for the treatment of cancer and nanoparticles-based drug delivery system as promising technology in microbial pharmaceutics and extensive applications. Other topics cover the structures of phytochemicals biological activities, microbial transformations of natural compounds in the advancement of steroid drugs, spherulites used as a carrier for drug delivery, and much more. Applied Pharmaceutical Science and Microbiology: Novel Green Chemistry Methods and Natural Products provides an abundance of new research on this increasingly important area."--
Antimicrobial, Antioxidant, and Composition of Verbena carolina and Mentha / Francisco Torrens and Gloria Castellano -- Recent Trends in Microbial Fermentation / Akshada Atul Bakliwal, Swati Gokul Talele, and Anil G. Jadhav -- Recent Reports on Imperative Medicinal Potentials of Boswellia serrate / Souranava Jana, Debarshi Kar Mahapatra, and Souvik Mukherjee -- Generation of Natural Pharmaceuticals Based on Microbial Transformation of Herbal Constituents / M.R. Badwar, Akshada A. Bakliwal, Swati Gokul Talele, and A.G. Jadhav -- Actinidia deliciosa: A Nature's Boon to Modern Pharmacotherapeutics / Vivek Kumar Raman, Sunil Kumar Chauhan, and Arijit Chaudhuri -- Ocimum sanctum L. (Holy Basil or Tulsi): A Medicinally Significant Herb / Manik Das, Debarshi Kar Mahapatra, and Kuntal Manna -- Anti-Proliferative Potentials of Silver Nanoparticles Synthesizedfrom Natural Biomass / Roshan Telrandhe, Sanjay Kumar Bharti, and Debarshi Kar Mahapatra -- Nanoparticles as a Promising Technology in Microbial Pharmaceutics / Eknath D. Ahire, Swati Gokul Talele, and Heena S. Shah -- Spherulites: A Novel Approach in Vesicular Drug Delivery System / Deepal J. Taank, Nayana Kale, Swati Gokul Talele, and Anil G. Jadhav -- Role of Omega-3 Fatty Acids in Different Neurodegenerative Disorders / Eknath D. Ahire, Khemchand R. Surana, Chandrashekhar D. Patil, Henna S. Shah, Ganesh B. Sonwane, and Swati Gokul Talele -- Thymoquinone: Therapeutic Potential and Molecular Targets / Abuzer Ali, Musarrat Husain Warsi, Wasim Ahmad, Mohd. Amir, Niyaz Ahmad, Amena Ali, and Abutahir.
OCLC-licensed vendor bibliographic record.
Keywords: Drug development; Pharmaceutical microbiology; Natural products; Green chemistry; MEDICAL / Pharmacology; SCIENCE / General